Small farm machinery to empower women and youth in the MFS - Ahmed, S.; Miajy, Abdullah; Haque, Abudul; Bhandari, Humnath (International Rice Research Institute, 2023)
Objectives: - To promote agricultural Mechanization. - Women and youth employment. - To overcome labour constraints in mixed farming systems.